Antibacterial Activity Test of Ethanol Extract of Spoon Leaves (Plantago major. L) Against Pseudomonas aeruginosa - Ira Jayani (Universitas STRADA Indonesia, 2020)
Typhoid is a bacterial infection disease of Pseudomonas aeruginosa. The irrationality of antibiotics against Pseudomonas aeruginosa is reported to trigger bacterial resistance, thus requiring an alternative antibacterial agent against typhoid. The diversity of Indonesian medicinal plants is still promising as a potential source of antibacterial agent, including sendok leaf. This study was aimed to determine antibacterial activity of ethanol extract of kacapiring leaves and its fractions against Pseudomonas aeruginosa. Subsequent fractionation was carried out using liquid-liquid partition method to obtain n-hexane, ethyl acetate, and etanol-water fractions. Antibacterial test was carried out using disk diffusion method to determine the diameter of inhibitory zone at concentrations of 10%, 15%, 20%, and 25%. The best antibacterial activity was revealed by residue fraction of 25% with inhibition zone diameter of 9,5 mm, respectively. Sendok have moderate antibacterial activity against Pseudomonas aeruginosa.